A study of price-volume relationship of trustee stocks in Singapore - Koh, Thong Mong (2014)
The liberalisation of CPF funds for investment under the Central Provident Fund (CPF) Approved Investment Scheme (AIS) occurred on May 3, 1986. Subsequently, there were other conversion of trustee stocks after they met the guidelines laid down. This report aims to analyse the effects of the conversion of a stock to trustee stock status. The effects will be analysed through the testing of abnormal returns and abnormal volume.